Case report: Umbilical vessel aneurysm thrombosis and factor V Leiden mutation leading to fetal demise - Oualiken, Camélia; Martz, Olivia; Idrissi, Nadia; Harizay, Fara Tanjona; Martin, Laurent; De Maistre, Emmanuel; Ricaud, Lou; Tarris, Georges (Frontiers in Medicine, 2023)
Complicated pregnancies are nowadays a major public health concern, with possible lethality or sequelae both for the mother and the fetus. Blood coagulation disorders (including antiphospholipid syndrome, factor V Leiden mutation and antithrombin deficiency) and hypertensive gestational disorders are very well-known contributors of complicated pregnancies with poor fetal outcome. Less commonly, vascular malformations of the placenta can also potentially lead to serious complications such as IUGR and fetal death. These malformations include hypercoiled umbilical cord, umbilical cord knot, umbilical cord varix, umbilical cord arterial or venous aneurysm, and velamentous insertion of the umbilical cord. Here, we report the case of a 29-year-old Gravida 2 Para 0 mother with previous history of stillbirth and smoking, admitted to the obstetrics department for the absence of fetal movement at 38 weeks of amenorrhea (WA). First-trimester and second-trimester routine ultrasounds were otherwise normal. Ultrasound performed at 37 WA revealed a 72 mm diameter cystic heterogenous mass at the umbilical cord insertion. After delivery, fetal pathology was otherwise normal, except for diffuse congestion and meconial overload suggesting acute fetal distress. Fetal karyotype was normal (46 XX). Placental pathology revealed an umbilical artery aneurysm (UAA) at the base of the insertion of the umbilical cord, lined with a CD34+ CD31+ endothelium, and filled with hemorrhagic debris, indicating aneurysm thrombosis. Maternal blood tests revealed heterozygous factor V Leiden mutation, without other associated auto-immune conditions (such as antiphospholipid syndrome). Umbilical artery aneurysms remain extremely rare findings in the placenta, with less than 20 reported cases. Umbilical artery aneurysms are usually located at the base of the insertion of the placenta and leading to fetal demise in more than 60% of cases, mainly due to aneurysmal thrombosis, hematoma, possible vascular compression and/or rupture. Umbilical vessel aneurysms can be associated with trisomy 18 or 13. In our case, the association of factor V Leiden mutation, a hypercoagulable state, with UAA could explain massive thrombosis of the aneurysmal lumen and sudden fetal demise. Further consideration of current guidelines for surveillance and management of UAA would allow appropriate planned delivery in maternal care settings.